2016
DOI: 10.17221/8666-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary starch types on rumen fermentation and blood profile in goats

Abstract: ABSTRACT:The objective of the present study was to investigate how feeding a diet containing a type of purified starch entirely produced from normal or high amylose maize grains would affect rumen fermentation and blood profile in goats. Twenty rumen-cannulated growing goats were assigned equally to one of two dietary treatments according to a randomized controlled trial design and fed two total mixed rations with similar ingredients and chemical composition except for the types of purified maize starch. One t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
3
10
1
Order By: Relevance
“…Leptin was not affected by the two diets in both species, as previously observed by Cannas et al [5] in mid-lactating sheep and by Wang et al [29] in dairy goats fed a normal or high-amylose starch at equal dietary starch concentrations. The lack of effect of diet could be related to the fact that leptin depends more on the overall energy balance than on the dietary source, as already observed by Cannas et al [5].…”
Section: Effect Of the Utilization Of High-starch And Low-starch Diet In Mid-lactation On The Evolution Of Metabolites And Hormonessupporting
confidence: 83%
See 1 more Smart Citation
“…Leptin was not affected by the two diets in both species, as previously observed by Cannas et al [5] in mid-lactating sheep and by Wang et al [29] in dairy goats fed a normal or high-amylose starch at equal dietary starch concentrations. The lack of effect of diet could be related to the fact that leptin depends more on the overall energy balance than on the dietary source, as already observed by Cannas et al [5].…”
Section: Effect Of the Utilization Of High-starch And Low-starch Diet In Mid-lactation On The Evolution Of Metabolites And Hormonessupporting
confidence: 83%
“…In previous studies on sheep, GH was higher with a low-starch diet than a high-starch diet (1.43 vs. 1.23 ng/mL; p < 0.02) [ 5 ], probably because the energy intake and balance were either higher in the high-starch diet or did not vary between high-starch and low-starch diets (3.28 vs. 3.83 ng/mL, respectively; p > 0.2) [ 6 ], and the dietary energy intake was similar between treatments. Growth hormone concentration in mid-lactating goats was higher for high-amylose starch (the least degradable starch at rumen level) than for normal starch diets (2.55 vs. 1.65 ng/mL; p = 0.06) at equal dietary starch concentrations [ 29 ], suggesting that GH is increased by diets that provide more rumen escape starch and, thus, higher intestinal glucose absorption. The higher GH concentrations observed in goats than in ewes are probably associated with the higher milk yield and lower energy balance, as suggested by the lower BCS accumulation, of goats in our experiment, confirming the important galactopoietic activity of this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Weak acidity provides the best conditions for rumen microorganisms to survive, which is conducive to the digestion and degradation of fibre and production of volatile fatty acids (Kingamkono et al 1994). Degradation of starch and cellulose by rumen microorganisms to produce volatile fatty acids will reduce the rumen pH, while the pH value of rumen would be increased by degrading protein and producing ammonia (Wang et al 2016;Asizua et al 2018). The BP has higher crude protein content than silage, but lower starch content.…”
Section: Meat Qualitymentioning
confidence: 99%
“…Other researchers reported hypoglycemia at the onset of lactation, especially in high-producing dairy goats, which are related to increasing milk lactose synthesis [ 32 , 33 ]. However, in diets containing high levels of fermentable starch, Wang et al [ 34 ] indicated high glucose concentration and a positive relationship between energy supplementation and serum glucose concentration. However, in our experiment, this relationship was not detected, possibly impaired by physiological variations, breed, or environmental conditions.…”
Section: Discussionmentioning
confidence: 99%